We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
141
1
avatar

why cos(pi)=-1 e cos(-pi)=-1 ???

 Mar 7, 2019
 #1
avatar+105327 
+2

I think this is

 

(-1)^[ cos(-pi) ]

 

Note that we have a trig identity that says    cos(theta) =  cos(-theta)

 

So....  cos (pi)  = cos(-pi)  = -1

 

So

 

(-1)^[cos(-pi)]  =

 

(-1)^{ -1 ]  =

 

1 / - 1  =

 

-1

 

 

cool cool cool 

 Mar 7, 2019

39 Online Users

avatar
avatar